2011
DOI: 10.1055/s-0031-1275400
|View full text |Cite
|
Sign up to set email alerts
|

Water-Tight Knee Arthrotomy Closure: Comparison of a Novel Single Bidirectional Barbed Self-Retaining Running Suture Versus Conventional Interrupted Sutures

Abstract: Standard medial parapatellar arthrotomies of 10 cadaveric knees were closed with either conventional interrupted absorbable sutures (control group, mean of 19.4 sutures) or a single running knotless bidirectional barbed absorbable suture (experimental group). Watertightness of the arthrotomy closure was compared by simulating a tense hemarthrosis and measuring arthrotomy leakage over 3 minutes. Mean total leakage was 356 mL and 89 mL in the control and experimental groups, respectively (p ¼ 0.027). Using 8 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 4 publications
2
34
0
1
Order By: Relevance
“…Accordingly, Nett et al [15] reported the superiority of tightness in arthrotomy closure with a barbed suture compared to a non-barbed suture, finding that after the simulation of a tense hemarthrosis, the barbed suture leaked 89 ml while the non-barbed suture drained 356 ml.…”
Section: Experimental Findingsmentioning
confidence: 99%
“…Accordingly, Nett et al [15] reported the superiority of tightness in arthrotomy closure with a barbed suture compared to a non-barbed suture, finding that after the simulation of a tense hemarthrosis, the barbed suture leaked 89 ml while the non-barbed suture drained 356 ml.…”
Section: Experimental Findingsmentioning
confidence: 99%
“…Barbed monofilament suture is being used more frequently as a result of its efficiency, cost savings, and improved or comparable wound closure outcomes [5, 7, 15-17, 19, 21, 23, 24, 26, 28]. The use of barbed monofilament suture for closure in a TKA has shown superiority in tightness of closure and failure analysis [16,24]. However, the barbed nature of this monofilament suture has the theoretical concern of the barbs acting as a place for bacteria to hide, resulting in higher infection rates if contaminated wounds are closed with barbed monofilament suture.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from cadaver knee studies suggests that bidirectional barbed sutures may provide a more watertight closure [6] and evidence from biomechanical testing suggests that TKAs closed with bidirectional barbed sutures are more resistant to failure than those where interrupted standard sutures have been used [12].…”
Section: Introductionmentioning
confidence: 99%